OVERVIEW OF THE METHODS AND TOOLS FOR ENVIRONMENTAL COMPONENTS MONITORING (Computer systems and information technologies, 2024)
Monitoring of environmental components is an important process for determining the level of pollution and tracking changes in the environment, and plays a key role in ensuring the health and comfort of residents, as well as in preserving the environment. Continuous monitoring of environmental components is key to ensuring human health, protecting nature and reducing the negative impact on the climate and ecosystems, as well as achieving sustainable development. In order to combat environmental pollution, it is necessary to implement effective measures to limit emissions of harmful substances, use environmentally friendly technologies and green solutions in all sectors of the economy, and raise public awareness of the problem of environmental pollution.From the analysis of the sources reviewed, a pattern was identified that the information technologies mainly used to monitor environmental components are either Internet of Things (IoT) technologies using modern sensors and data transmission components or artificial intelligence technologies such as computer vision. Less commonly, the use of robots, UAVs, and digital twins is being traced.Based on a critical analysis of methods and tools for environmental components monitoring, there is a need to develop such methods and tools for environmental components monitoring that would: perform cheaper and more versatile environmental components monitoring than existing analogues, but at the same time have no less accuracy and speed; monitor the state of the environment; identify sources of environmental pollution; warn of environmental disasters; assess the state of natural resources; support environmental decision-making; collect and analyze various environmental indicators in real time; assessed the level of quality and safety of environmental components, which will allow immediate response to quality changes and promptly take the necessary measures, etc., which will be the focus of the authors' further efforts.
Keywords: monitoring of environmental components; methods of monitoring environmental components; tools of monitoring environmental components; Internet of Things; artificial intelligence technologies